Characteristics of children presenting with new onset diabetes and DKA in the COVID-19 pandemic: a national cohort study - Ponmani, Caroline; Roland, Damian; Lyttle, Mark D.; Barrett, Michael; Hulse, Tony; Nijman, Ruud G. (Frontiers in Disaster and Emergency Medicine, 2024)
Objectives The objective of this study was to evaluate the characteristics of children presenting with new onset diabetes and diabetic ketoacidosis (DKA) in the first COVID pandemic year, compared to pre-pandemic evidence and identify the factors associated with DKA at diagnosis. Design Retrospective medical record review. Setting Forty-nine pediatric Emergency Departments (EDs) across the UK and Ireland. Patients All children aged 6 months to 16 years presenting to EDs with new onset diabetes and DKA, during the COVID-19 pandemic (1 March 2020–28 February 2021) and the preceding year (1 March 2019–28 February 2020). Results There were increases in children presenting with new onset diabetes in DKA (395–566, 43%) and severe DKA (141–252, 79%) in the first COVID pandemic year, with patient characteristics similar to the pre-pandemic period. Healthcare seeking delay did not appear to be the sole contributing factor to DKA during the COVID pandemic. The median duration of symptoms of 14 days for both children who presented with and without DKA and were similar across both years; those in severe DKA had shorter median duration of 7 days (IQR: 5–21 days). Conclusions There were significant increases in children with new onset diabetes presenting with DKA in the first COVID pandemic year. Increased DKA rates and severity despite a constant median symptom duration suggest a multifactorial process. Studies to determine checkpoints for intervention between symptom onset and diagnosis of diabetes are vital to mitigate the high incidence of DKA in new onset diabetes.